1999
DOI: 10.1210/mend.13.1.0224
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Activation of Mitogen-Activated Protein Kinase via Somatostatin Receptor 1 (SSTR1)

Abstract: Hormones and growth factors regulate cell growth via the mitogen-activated protein (MAP) kinase cascade. Here we examine the actions of the hormone somatostatin on the MAP kinase cascade through one of its two major receptor subtypes, the somatostatin receptor 1 (SSTR1) stably expressed in CHO-K1 cells. Somatostatin antagonizes the proliferative effects of fibroblast growth factor in CHO-SSTR1 cells via the SSTR1 receptor. However, in these cells, somatostatin robustly activates MAP kinase (also called extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
1
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 87 publications
7
91
1
7
Order By: Relevance
“…First, agonist binding to the sst1 receptor is completely resistant to GTP inhibition after pertussis toxin treatment of CHO-K1 cells (17). Second, all sst1-mediated signaling in CHO-K1 cells, including cyclase inhibition, inositol 1,4,5-trisphosphate formation, tyrosine phosphatase stimulation, and mitogen-activated protein kinase activation are blocked by pertussis toxin (15,20,44). Together, these observations provide strong support for the conclusion that the sst1 receptor is coupled exclusively to pertussis toxin-sensitive G proteins in this cell line.…”
mentioning
confidence: 99%
“…First, agonist binding to the sst1 receptor is completely resistant to GTP inhibition after pertussis toxin treatment of CHO-K1 cells (17). Second, all sst1-mediated signaling in CHO-K1 cells, including cyclase inhibition, inositol 1,4,5-trisphosphate formation, tyrosine phosphatase stimulation, and mitogen-activated protein kinase activation are blocked by pertussis toxin (15,20,44). Together, these observations provide strong support for the conclusion that the sst1 receptor is coupled exclusively to pertussis toxin-sensitive G proteins in this cell line.…”
mentioning
confidence: 99%
“…There are six SS receptors, all of which are G-protein coupled receptors (GPCRs) (3,4), which couple through G i/o . SS transduces its physiological signal through many effectors, which include adenylyl cyclase (5), inwardly rectifying K Ï© channels (6), tyrosine phosphatase (7), phospholipase C (8), voltage-dependent Ca 2Ï© channel (9), Na Ï© -H Ï© antiporter (10), and mitogen-activated protein kinase (11). We recently reported that SS can activate phospholipase D (PLD), causing a subsequent increase in phosphoinositol 4,5-bisphosphate (PIP 2 ) concentration (12).…”
Section: Somatostatin (Ss)mentioning
confidence: 99%
“…Both PKC isoforms are known to enhance the activity of PLD. GPCR activation of small G-proteins can be involved in stimulating PLD (6,11). The signaling mechanisms responsible for small G-protein regulation of PLD are diverse, but two small G-proteins, Rho and Arf, have been firmly established to regulate PLD activity through GPCRs (26,(32)(33)(34)(35)(36).…”
Section: Somatostatin (Ss)mentioning
confidence: 99%
“…[11] The direct mode of action involves interaction with somatostatin receptors on tumor cells leading to activation of phosphotyrosine phosphatases [12] and modulation of the mitogen-activated protein kinase signaling pathway. [13] The indirect antiproliferative effect occurs through inhibition of expression of growth factors, such as insulin-like growth factor and vascular endothelial growth factor. [14] Activities of SSAs are mediated by interaction of somatostatin with a series of five receptors (SSTRs) encoded by five different genes belonging to the class of receptors linked to transmembrane G-proteins, able to inhibit cAMP.…”
Section: Introductionmentioning
confidence: 99%